De Novo Focal and Segmental Glomerulosclerosis After COVID-19 in a Patient With a Transplanted Kidney From a Donor With a High-risk APOL1 Variant. Issue 1 (January 2021) - Oniszczuk, Julie; Moktefi, Anissa; Mausoleo, Aude; Pallet, Nicolas; Malard-Castagnet, Stephanie; Fourati, Slim; El Karoui, Khalil; Sahali, Dil; Stehlé, Thomas; Boueilh, Anna; Verpont, Marie-Christine; Matignon, Marie; et al.
Abstract : Background: There is compelling evidence that renal complications in a native kidney are a major concern in patients infected with severe acute respiratory syndrome coronavirus 2, the causal agent of coronavirus disease 2019 (COVID-19). The spectrum of renal lesions observed on renal grafts in this context remains to be determined. Methods: We report the case of a renal transplant recipient with non-severe COVID-19, who subsequently developed nephrotic syndrome associated with acute renal injury. Results: Renal biopsy demonstrated focal and segmental glomerulosclerosis lesions classified as not otherwise specified histological variant. Genotyping for 2 risk alleles of the apolipoprotein L1 gene demonstrated that the donor was homozygous for the G2/G2 genotype. Conclusions: In renal transplant patients receiving kidneys from donors with high-risk apolipoprotein L1 variants, COVID-19 may promote acute glomerular injury in the form of focal and segmental glomerulosclerosis.